Development of Th17‐Associated Interstitial Kidney Inflammation in Lupus‐Prone Mice Lacking the Gene Encoding STAT‐1. Issue 5 (27th April 2016) - Yiu, Gloria; Rasmussen, Tue K.; Ajami, Bahareh; Haddon, David J.; Chu, Alvina D.; Tangsombatvisit, Stephanie; Haynes, Winston A.; Diep, Vivian; Steinman, Larry; Faix, James; Utz, Paul J.
Abstract : Objective: Type I interferon (IFN) signaling is a central pathogenic pathway in systemic lupus erythematosus (SLE), and therapeutics targeting type I IFN signaling are in development. Multiple proteins with overlapping functions play a role in IFN signaling, but the signaling events downstream of receptor engagement are unclear. This study was undertaken to investigate the roles of the type I and type II IFN signaling components IFN‐α/β/ω receptor 2 (IFNAR‐2), IFN regulatory factor 9 (IRF‐9), and STAT‐1 in a mouse model of SLE. Methods: We used immunohistochemical staining and highly multiplexed assays to characterize pathologic changes in histology, autoantibody production, cytokine/chemokine profiles, and STAT phosphorylation in order to investigate the individual roles of IFNAR‐2, IRF‐9, and STAT‐1 in MRL/ lpr mice. Results: We found that STAT‐1 −/− mice, but not IRF‐9 −/− or IFNAR‐2 −/− mice, developed interstitial nephritis characterized by infiltration with retinoic acid receptor–related orphan nuclear receptor γt–positive lymphocytes, macrophages, and eosinophils. Despite pronounced interstitial kidney disease and abnormal kidney function, STAT‐1 −/− mice had decreased proteinuria, glomerulonephritis, and autoantibody production. Phosphospecific flow cytometry revealed shunting of STAT phosphorylation from STAT‐1 to STAT‐3/4. Conclusion: We describe unique contributions of STAT‐1 to pathology in different kidney compartments in a mouse model, and provide potentially novel insight into tubulointerstitial nephritis, a poorly understood complication that predicts end‐stage kidney disease in SLE patients.